Pengaruh Pengisian Pasir dan Lilin terhadap Kualitas Pembentukan Batang Silinder Pipa - Surahto, Aep; Laura, Novi; Perdi, Perdi (Prosiding Seminar Nasional Teknoka, 2016)
Iron pipes are widely used in everyday life. At their role will be found a few problems. Based on some of the issues that arise, this research will discuss the problem of cracks. Selection of cracks due to the aftereffect that could result in a loss bebarapa both in terms of material and function. This study addressed the issue of changes in the form of 0.5-inch diameter pipe in the pipe thickness of 1.2 mm and 1.8 mm were exposed to stress (stress) during the bending process. In each pipe treated; without stuffing pipe, a pipe filled with sand and a candle stuffing pipe. In each pipe bend with an angle of 90 Â°. After that, the pipe is cut to determine the condition of each pipe bends. The test results in getting that on the pipe diameter of 1.2 mm change very drastically and the elbow pipe diameter of 1.8 mm changes are not too drastic changes shape. The thickness of the pipe will influence changes in the results of elbow pipe diameter, the thicker the better the pipe diameter.